Celebrating Christine Watkins' 40th Birthday at Good body's - Watkins, Howard::::::::: (1989)
Helen James, Sally Kayser, Maril Turpin, Frances Kamp, Howard Watkins, Robin Watkins, Christine Watkins, Shirley Griffenhagen, Leslie Prusia, and Peggy Sanders